“Comportamiento agronómico del frejol (Phaseolus vulgaris l.)con dos abonos orgánicos en la época seca.” - Bodero Aguayo, Nelson Alberto (2023)
The investigation was carried out at the farm of Mr. Bodero Jacobo with the purpose of evaluating the pata paloma beans (Phaseolus vulgaris L.). The farm is located in San Pablo N° 1 precinct which belongs to Valencia canton, Los Rios province. The objective was to evaluate the agronomic behavior of beans (Phaseolus vulgaris L.) with two organic fertilizers in the dry season. Two fertilizers (biol and leachate humus) were applied with a duration of 145 days, the data was taken after 14, 28, and 42 days. The evaluated variables were: germination percentage (%), plant height (cm), days to flowering, number of pods, and production weight (kg). A complete randomized block design was used (CRBD) with four treatments and five repetitions with 33 plants as experimental units. The results showed that the application of doses of biol and leachate humus in combination of 140 ml presented the best results in the variables: plant height with an average of 85,80 cm after 42 days; it was reduced the days to flowering with an average of 32,56 days; the number of pods increased with an average of 14,29 days, and the production weight with 1,28 kilograms. The best benefit/cost ratio was obtained with the treatment biol + leachate humus with 0,23.